Antioxidant activity of Tween‐20 and Tween‐80 evaluated through different in‐vitro tests. (31st December 2014) - Pérez‐Rosés, Renato; Risco, Ester; Vila, Roser; Peñalver, Pedro; Cañigueral, Salvador
Abstract: Objectives: This study aimed to evaluate the possible antioxidant activity of Tween‐20 and Tween‐80, two amphipathic nonionic surfactants commonly used as solubilizers and stabilizers, whose pharmacological effects have been ignored to a large degree. Methods: Antioxidant activity was investigated in vitro measuring the scavenging activity on the stable free radical 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH ● ), the production of reactive oxygen species (ROS) in activated human neutrophils using flow cytometry and the myeloperoxidase (MPO) inhibitory activity. Key findings: Tween‐20 and Tween‐80 did not show scavenging activity on DPPH ●, while produced a decrease of the ROS production in human neutrophils, being Tween‐20 more active than Tween‐80. Moreover, Tween‐80 and Tween‐20 were found to significantly stimulate MPO enzymatic activity. Conclusions: Our findings raise concerns with regard to the indiscriminate use of Tween‐20 and Tween‐80 in clinical and laboratory testing, since they could influence the results that are assigned to the tested substance.